Evaluation of results of minimally invasive per cutaneous surgeries in management of calcaneal fractures - Parikh, Kushal Nikhil; Moradiya, Nirav; Shah, Shalin; Khodifad, Ankit (International Journal of Research in Orthopaedics, 2018)
Background: To analyze the outcome percutaneous surgeries in fractures of the calcaneum. Methods: 20 patients admitted in a tertiary care center in Ahmedabad were followed up from admission to until 2 years post operatively and functional outcomes in them following operative intervention were analyzed using AOFAS and Maryland scoring system. Results: Majority of patients have excellent or good outcome following percutaneous surgery in fractures of the calcaneum. The results were evaluated for 22 people with intraarticular calcaneum fractures using the Maryland foot score and AOFAS score. The mean AOFAS score was 86. There were 6 excellent, 12 good and 4 fair results. Conclusions: Percutaneous fixation in fractures of the calcaneum is a middle path in treatment of calcaneum fracture having the benefit of better reduction of ORIF plating and lesser soft tissue injury or chances of infection of conservative management.